Application of paclobutrazol to lengthen fruiting season in durian (Durio zibethinus) - Hasan, B. M.; Karim, M. Z. (1989)
The intensity of cropping classifies durian as having a biennial bearing habit. Various cultural methods have been attempted to make durian bear fruits during the minor season or the low yield year. Investigation is made on the use of paclobutrazol as a stimulant for flower and fruit production. Results of the experiment reported here shows that paclobutrazol can increase flowering and fruiting and can be applied at any time of the year. However, further investigations are needed before the chemical can be recommended for an extensive use.